Impairments in Fast Axonal Transport and Motor Neuron Deficits in Transgenic Mice Expressing Familial Alzheimer's Disease-Linked Mutant Presenilin 1 - Lazarov, Orly (Society for Neuroscience, 2007)
Presenilins (PS) play a central role in γ-secretase-mediated processing of β-amyloid precursor protein (APP) and numerous type I transmembrane proteins. Expression of mutant PS1 variants causes familial forms of Alzheimer's disease (FAD). In cultured mammalian cells that express FAD-linked PS1 variants, the intracellular trafficking of several type 1 membrane proteins is altered. We now report that the anterograde fast axonal transport (FAT) of APP and Trk receptors is impaired in the sciatic nerves of transgenic mice expressing two independent FAD-linked PS1 variants. Furthermore, FAD-linked PS1 mice exhibit a significant increase in phosphorylation of the cytoskeletal proteins tau and neurofilaments in the spinal cord. Reductions in FAT and phosphorylation abnormalities correlated with motor neuron functional deficits. Together, our data suggests that defects in anterograde FAT may underlie FAD-linked PS1-mediated neurodegeneration through a mechanism involving impairments in neurotrophin signaling and synaptic dysfunction.